Cool cities : urban sovereignty and the fix for global warming - Barber, Benjamin R., 1939-2017 (New Haven ; London : Yale University Press, 2017)
A pointed argument that cities-not nation-states-can and must take the lead in fighting climate change. Climate change is the most urgent challenge we face in an interdependent world where independent nations have grown increasingly unable to cooperate effectively, even on the urgent issue of sustainability. Can cities do better? Benjamin R. Barber argues that with more than half the world's population, 80 percent of both its GDP and its greenhouse gas emissions, and a common will to cooperate, they can. In this compelling sequel to If Mayors Ruled the World, Barber assesses both broad principles and specific strategies like fracking bans, walkable cities, above-ground mining of precious resources, energy and heating drawn from garbage incineration, downtown wind turbines, and skyscrapers built from wood. He shows how cities working together on climate change can find common measures by which to evaluate the radically different policies they pursue. This is a book for a world in which combating climate change is about nothing less than cities' survival.
Introduction : politics not science -- Part One. Making politics work for science. The social contract and the rights of cities -- The devolution revolution and the politics of COP 21 -- Climate change in the anthropocene -- The facts are mute, money talks -- Privatization and market fundamentalism -- Political institutions old and new : cities not nation-states -- The road to global governance -- Climate justice : making sustainability and resilience complementary -- The end of sovereignty redux : a global parliament of mayors -- Part Two. Making democracy work for politics. Common principles and urban action -- The politics of commensurability and the challenge of trust -- City sovereignty and the need for urban networks -- A practical climate action agenda -- Exemplary cities -- Trust among cities : an index of commensurability -- Realizing the urban climate agenda.
Includes bibliographical references (pages 177-193) and index.
Keywords: City planning -- Environmental aspects; Global warming; Cities and towns -- Growth; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; POLITICAL SCIENCE / Public Policy / Environmental Policy; SCIENCE / Global Warming & Climate Change; Cities and towns -- Growth; City planning -- Environmental aspects; Global warming